2014
DOI: 10.1371/journal.pone.0084590
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve in Young and Old Healthy Subjects: Differences and Similarities in a Testing-the-Limits Paradigm with DSST

Abstract: Cognitive reserve (CR) is understood as capacity to cope with challenging conditions, e.g. after brain injury or in states of brain dysfunction, or age-related cognitive decline. CR in elderly subjects has attracted much research interest, but differences between healthy older and younger subjects have not been addressed in detail hitherto. Usually, one-time standard individual assessments are used to characterise CR. Here we observe CR as individual improvement in cognitive performance (gain) in a complex tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 53 publications
3
21
2
2
Order By: Relevance
“…Overall, the present results are consistent with those of our previous study [16] and favor the evidence that activation of cognitive resources is well preserved in the healthy elderly, notwithstanding individual differences in performance gains. In this study, performance gain in the DSST testing-the-limits paradigm was 15.53 items (SD = 6.03), as compared to 18.94 items (SD = 7.30) in our earlier study [16].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Overall, the present results are consistent with those of our previous study [16] and favor the evidence that activation of cognitive resources is well preserved in the healthy elderly, notwithstanding individual differences in performance gains. In this study, performance gain in the DSST testing-the-limits paradigm was 15.53 items (SD = 6.03), as compared to 18.94 items (SD = 7.30) in our earlier study [16].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, performance gain in the DSST testing-the-limits paradigm was 15.53 items (SD = 6.03), as compared to 18.94 items (SD = 7.30) in our earlier study [16]. Interestingly, the younger group (20-30 years) in our earlier study [16] showed a higher gain (25.52), but variability was in a similar range (SD = 10.10).…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations